An on-package colorimetric sensing label based on a sol-gel matrix for fish freshness monitoring. (1st March 2020) - Liu, Xiuying; Chen, Keke; Wang, Jiayan; Wang, Yu; Tang, Yiwei; Gao, Xue; Zhu, Lijie; Li, Xuepeng; Li, Jianrong
Highlights: On-package colorimetric sensing label was developed for fish freshness. Label was based on bromocresol green indicator and sol-gel matrix layer. A Hue Saturation Value model was used to correlate the response of sensing label. Three kinds of fish fillets showed intense color change during the spoilage trial. Abstract: Fish freshness monitoring is important for consumers. This study aims to develop an colorimetric sensing label based on bromocresol green (BCG) and a sol-gel matrix layer coated onto filter paper to monitor fish freshness. Characterization results showed that the sol-gel layer was successfully coated, and the coating yield was 14.25%. The fish freshness could be detected clearly by the naked eye as the color of the sensing label changed. A Hue Saturation Value (HSV) model was used to correlate the response of the sensing label to the freshness of fish samples. Hue (H) values showed a linear response to the total volatile basic nitrogen (TVB-N) concentration in the range of 16.4–23.11 mg/100 g at room temperature, and in the range of 9.28–24.12 mg/100 g at a chilled temperature. The sensing label was applied to other types of fish, and showed an intense color change during the spoilage trial.